CO Isotopologue-derived molecular gas conditions and CO-to-H2 conversion factors in M51 - Brok, Jakob den; Jiménez-Donaire, María J.; Leroy, Adam; Schinnerer, Eva; Bigiel, Frank; Pety, Jérôme; Petitpas, Glen; Usero, Antonio; Teng, Yu-Hsuan; Humire, Pedro; Koch, Eric W.; Rosolowsky, Erik; et al. (The astronomical journal)
Over the past decade, several millimeter interferometer programs have mapped the nearby star-forming galaxy M51 at a spatial resolution of ≤170 pc. This study combines observations from three major programs: the PdBI Arcsecond Whirlpool Survey, the SMA M51 large program, and the Surveying the Whirlpool at Arcseconds with NOEMA. The data set includes the (1-0) and (2-1) rotational transitions of 12CO, 13CO, and C18O isotopologues. The observations cover the r < 3 kpc region, including the center and part of the disk, thereby ensuring strong detections of the weaker 13CO and C18O lines. All observations are convolved in this analysis to an angular resolution of 4″, corresponding to a physical scale of 170 pc. We investigate empirical line ratio relations and quantitatively evaluate molecular gas conditions such as temperature, density, and the CO-to-H2 conversion factor (α CO). We employ two approaches to study the molecular gas conditions: (i) assuming local thermodynamic equilibrium (LTE) to analytically determine the CO column density and α CO, and (ii) using non-LTE modeling with RADEX to fit physical conditions to observed CO isotopologue intensities. We find that the α CO values in the center and along the inner spiral arm are ∼0.5 dex (LTE) and 0.1 dex (non-LTE) below the Milky Way inner disk value. The average non-LTE α CO is 2.4 ± 0.5 M ⊙ pc−2 (K km s−1)−1. While both methods show dispersion due to underlying assumptions, the scatter is larger for LTE-derived values. This study underscores the necessity for robust CO line modeling to accurately constrain the molecular interstellar medium’s physical and chemical conditions in nearby galaxies.